Extração de compostos bioativos das sementes de urucum utilizando tecnologias combinadas - Taham, Thiago (2015)
extracted from annatto seeds using alkaline solutions, organic solvents or friction in heated vegetable oil. These methods require a subsequent unit operation of bixin separation and can generate toxic waste. Thus, the demand for more environmentally attractive solutions leads to the study of the alternative extraction technologies, such as mechanical extraction or using supercritical fluids. This study aimed to investigate the extraction of bioactive compounds of the annatto seeds, with the focus on bixin, using different technologies. The extractions were conducted in a fixed bed using supercritical CO2, water and ethanol as solvents in conventional, sequential and combined extractions. The mechanical extraction of seeds in a screen-topped spouted bed unit was also studied, using tools of experimental design and process optimization in order to identify the conditions of the best extraction efficiency (for the powder and the bixin) and higher purity of the powder obtained. The use of ethanol at ambient pressure in the fixed bed extraction was responsible for the higher yields of bixin and the highest percentages of this compound in the extracts obtained, among all tested conditions. On the other hand, it could be noticed that the pretreatment of seed, using supercritical CO2, resulted in the extraction of an oil rich in -tocotrienol and geranylgeraniol with low impact in the bixin yield obtained in a sequential extraction using ethanol at low pressure. The experimental study of mechanical extraction in a spouted bed unit, in turn, resulted in an annatto powder with variable contents of bixin, but always commercially attractive (over 30% of bixin). Using the optimization process, the conditions that led to the best extraction efficiency (for powder and bixin) and greater purity powder (above 65%) were identified. The combination of sequential extraction of the studied technologies, spouted bed and extraction in fixed bed using ethanol maximized the performance of bixin extraction, near the yield obtained with chloroform. This fact indicates that the sequential extractions can be a good alternative processing, allowing maximum utilization of the dye present in the seeds, when compared with technologies studied separately.